Integrating ARI prevention with micro credit programme: experience of BRAC, Bangladesh - Hadi, Abdullahel (BRAC Research and Evaluation Division (RED), 2019)
The contribution of ARI control project within the framework of micro credit-based development intervention in promoting maternal knowledge of acute respiratory infections (ARIs) in children was assessed. Data came from a cross-sectional survey of 2,814 mothers of under 5 year-old children residing in 200 randomly selected villages in five districts in Bangladesh. Findings revealed that the ARI control project had significant positive effects in raising knowledge of clinical signs and preventive measures. When ARI control project activities were integrated with the credit-based development initiative, maternal knowledge improved even further. The study concludes that the micro-credit programme can be a catalytic agent in raising health knowledge among the poor women in developing countries.